Industrial safety control, non invasivet - Quintero-Rosas, Verónica (2016)
The industry currently has a wide range of processes that operate with precision and accuracy achieved after years of development on technology, commonly algorithms that control industrial machinery seeking to emulate the efficiency of human labor but in turn increase the speed and accuracy of processes, an algorithm or a robot despite being scheduled and essentially by man has no conscience, his actions are defined by guidelines established by the operator, within this includes everything related to security, due to the high penetration with automated equipment in various industrial fields, especially in assistance to perform tasks that are at high risk for a person and require human skill to take place, the integrity of the operators of this type of equipment is considered a very important point to develop. Apply security techniques in automated elements using body sensor recognition brings us a little closer to something that seems impossible, to raise awareness machines.